WEBINAR MENGENAI KONSEP ILMU FALAK DAN MEMPRAKTEKKAN TATA CARA MENGHITUNG ARAH KIBLAT - Muhammad Fauzi Alamsyah; Yoyo Hambali; Musyafa Amin Ash Shabah (LPPM Universitas Islam 45, 2022)
Prayer times are basically determining the daily position of the sun. The movement of the sun which is the standard of prayer times is the concern of Muslims throughout the ages. Astronomy as part of astronomy is useful for general knowledge and worship. The benefits of Falak science in worship are determining the Qibla direction, prayer times, the beginning of the month and eclipses. Therefore, this community service activity is important to do in order to increase confidence in worship and straighten people's understanding. The implementation method is in the form of Webinar counseling using the Zoom meeting platform. The results of this activity are increasing insight into the concept of astronomy and being able to practice the concept of astronomy in daily activities.